Analysis of the Perceived Motivations behind the Activities of Tertiary Students on Social Media - Yusuf, Clancy (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Social media has been regarded as one of the most phenomenal innovations in the information and technology space. The platforms, Facebook, Instagram, Snapchat, Blogs among others, have become a way of socializing, communicating, and interacting across borders. However, mobile phones have made social media access easier, this is as a result of its ability to connect to the internet as well as the compatibility of the platforms on these mobile devices. This, in turn, creates an opportunity for communication on the move, as users are able to connect with their friends at any point and place. This study conducts a quantitative analysis into the use of social media by finding out the motivations behind posting, liking and sharing social media contents by youths. This research is conducted in the Spring Semester of the 2017/2018 academic session among the 376 registered undergraduate students of the Eastern Mediterranean University. Findings of this study reveal that some social media users follow others because they have been followed by the same user/s. This will reciprocate the gesture and as such might be the beginning of an online/offline friendship. Results reveal that some social media users just comment on other users' platforms for fun. Findings also indicate that there is a statistically significant difference between the age group of youth that like one another’s posts on social media. Keywords: Social media, Youth, Motivation, University, Students.

ÖZ: Sosyal medya, bilgi ve teknoloji alanındaki en önemli yeniliklerden biri olarak nitelendirilmektedir. Facebook, instagram, snapchat, bloglar ve bunlar gibi bir çok platform sosyalleşme, iletişim ve sınırların ötesinde etkileşim yolları haline gelmiştir. Fakat, cep telefonları sosyal medyaya ulaşımı daha kolay hale getirmiştir, bu da internete bağlanabilme yeteneği yanında bu platformların cep telefonlarına uyumlu olmasının sonucudur. Bu da kullanıcıların arkadaşlarıyla herhangi bir nokta veya yerde bağlantı kurabilmeyle, hareket halinde iken iletişime fırsat yaratmaktadır. Bu çalışmada sosyal medya kullanımı hakkında bir nicel analiz uygulanarak içeriklerinin gençler tarafından bildirim, beğeni ve paylaşım motivasyonları araştırılmaktadır. Araştırma 2017-2018 akademik döneminin bahar döneminde, 376 kayıtlı Doğu Akdeniz Üniversitesi lisans öğrencisi ile gerçekleştirilmiştir. Bu çalışmanın bulguları bazı sosyal medya kullanıcılarının başkalarını takip etme sebeplerinin bu kişiler tarafından takip edilmek olduğunu göstermiştir. Bu jestine karşılık vererek çevrim içi çevrim dışı arkadaşlıkların başlangıcına dönüşebilmektedir. Araştırma sonuçları bazı sosyal medya kullanıcılarının platformlarına sadece eğlence için yorum yaptıklarını göstermiştir. Sonuçlar aynı zamanda birbirlerinin bildirimlerini sosyal medyada beğenen genç gruplar arasında istatistiksel olarak anlamlı bir farklılık olduğunu da göstermektedir. Anahtar Kelimeler: Sosyal medya, Gençlik, Motivasyon, Üniversite, Öğrenciler
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2018. Supervisor: Assoc. Prof. Dr. Bahire Efe Özad.
Keywords: Communication and Media Studies; Social Media--Communication--International Students--Eastern Mediterranean University--Cyprus, North; Social media; Youth; Motivation; University; Students